Experimental study on three-dimensional electrode-electrode-Fenton coupling for emulsified oily wastewater treatment - ZHANG Hua; HU Chuanlong; WU Di; YANG Wenxin; XUE Jia; ZHANG Wenyi (Gongye shui chuli)
The emulsified oily wastewater generated from machining processes has complex organic components and poor biodegradability. Nanoscale zero-valent iron, activated carbon, and glass beaded mixed particles were used as particle electrodes to construct a three-dimensional electrode-electro-Fenton coupling system to effectively treat the wastewater. The effects of cathode plate material, particle electrode ratio, voltage, pH, electrode spacing, aeration rate, and other factors on the removal efficiencies of total oil and COD in emulsified oily wastewater were researched. The results showed that pH, electrode spacing, aeration rate, and voltage were the main effect factors, with the order of pH>electrode spacing>aeration rate>voltage. The three-dimensional electrode-electro-Fenton system was used to treat emulsified oily wastewater with COD of 1 030 mg/L and total oil of about 150 mg/L. Under the conditions of voltage of 25 V, activated carbon, nanoscale zero-valent iron, and glass bead dosages of 60, 20, and 20 g/L, pH=3, electrode plate spacing of 6 cm, aeration rate of 1.0 L/min, and electrolyte Na2SO4 concentration of 4 g/L, the pollutant removal effect was optimal, with COD and total oil removal rates reaching up to 89.95% and 93.97%, respectively. GC-MS analysis showed that the three-dimensional electrode-electro-Fenton system could oxidize, break, and decompose long-chain and short-chain petroleum hydrocarbons in emulsified oily wastewater into smaller organic compounds, and they were even mineralized into carbon dioxide and water. Technical and economic analysis showed that this process had certain cost advantages and had prospects for promotion and application.